(untitled) (Revista de Ensino em Artes, Moda e Design, 2021)
We live in an accelerated future, as the futurologists have been saying. In fact, the temporality instituted by the pandemic anticipates many changes that were already underway, such as the institutionalization of homework, online education, the even greater relevance of sustainability in its broadest sense and the social demand for companies and brands to be more socially responsible. Other changes, that have been embryonic up to now, become more evident, such as the strengthening of values of solidarity and empathy, the transformation of individual practices into collective actions – staying at home and using mask are also used as a practice of collective respect, concern to others –, in addition to questioning the economic models themselves, such as the proposal of shifting shareholder capitalism, focusing exclusively on financial and short-term, into another dynamic that takes into account all stakeholders, accelerating the criticisms of the society model based on hyperconsumption. Within these profound transformations, new professions, new ways of life, new ways of teaching and learning are being established. Valuing experiences, reinforcing ways of life that contribute to a more just and solidary society, will become even more relevant in a pandemic and post-pandemic world. At a time when empathy is so valued, reestablishing the most basic forms of relationship between people becomes indeclinable, highlighting collective attitudes that dignify the subject, understanding his life story. Renegotiating new collective and group actions becomes primordial, which includes new ways of learning, teaching and coexisting. That is what education needs right now. A perspective of respect for the subject’s path, for life narratives, not only transporting the teaching-learning process into digital platforms, which is not exactly new. In this moment of subverted daily lives, of digitized spaces, of “visible” inequalities, of disconnected connectivity, it is necessary to develop a process of trust that gives meaning to the “new” relationships between teacher, student, teaching (as a substance to be apprehended and learned) and technologies. Trying to adjust to the time, making sense of the senseless moment. Losing the fear of interacting, trusting the other as a partner in the process of reciprocal construction of knowledge when faced with remote, virtual classes, in “supervisibility” discussion spaces, initiatives that may even be experienced as a normal life practice, for some, but certainly arousing much concern for others. The objective of this article is to briefly understand and analyze the challenges faced by education in Brazil in this current pandemic moment and, at the same time, to propose methodological paths that can address such challenges regarding to the technological issues that education, in digital environments, creates and establishes both for teachers and students – and, eventually, for their families –, in the face of regarding social, cultural and educational inequalities, which this present time has been intensifying, as well as facing an inevitable new scenario for technological university education, which will need to be rewritten in the postpandemic context. As it is observed today, and as it will possibly be observed in the near future, not everyone can travel to higher education centers and, in this way, it is also proposed, in this work, to think about a methodology based on use of Digital Information and Communication Technologies (DICT) in university technological education, which is commonly excluded from more consistent discussions in relation to the teaching-learning process, although considering the incorporation of technologies within a more humanistic, sensitive and welcoming view. Sometimes, the geographical hierarchy ends up centralizing what should be decentralized, such as democratizing access to quality education for all. In this aspect, and in confronting the social injustices demarcated, also by the territoriality, it is that a “look broadly”, a “learn collectively”, can impact in more solidary and respectful attitudes, with broad, unrestricted and inclusive participation. This new form of interaction, teacher-student-technology, moves towards a minimally consistent methodological proposal to face the challenges of the current moment of university technological education. Thus, the dialogue was established between the Pedagogy of Autonomy, by the educator Paulo Freire, defender of a pedagogy founded on ethics, respect, dignity and autonomy of the student, and the interaction regimes - and even of regimes of sense - from Eric Landowski’s sociosemiotics, trying to understand the new teaching practices that are being established sometimes in the mediated presence of teacher and student, sometimes in their virtualized presences, in an asynchronous way, in a path that, at this moment, is set as necessary. Therefore, it will be sought, in a brief way, to associate the elementary forms of educational practices, from the perspective of socio-semiotics, from Landowski’s interactional regimes, to Freire’s criticality of curiosity. In other words, a knowledge produced in action, a "blooming" in the interaction, which puts in relationship the naive curiosity with criticism to a knowledge, to an "awakening", to a passion to know, transforming this knowledge, as Freire says, into an epistemological curiosity, in a related knowledge that motivates a broader understanding of reality. Know the own space, reflect on it and provoke changes through out a systematized knowledge, with constant debates, valuing the individual and his path, in line with the teaching contents. In these new mediated and virtualized interactions, in which different types of distances are observed between people, inclusion, in the broad sense of the term, becomes fundamental and should generate a space for social well-being, motivating practices that foster more human educational actions in the face of all digital transformation, with an irresistibility to the values of cooperation, tolerance and mutual respect; welcoming actions, therefore. Thus, it is necessary to promote social inclusion actions for the transformation and respect for the community at this unique moment. The OFÉ Institute was created in this direction, objecting to offer high quality education, to be a reference in university technological professional education, based on innovation, social justice, sustainable, participatory and ethical management, in order to promote local and regional development by means of a humane, sensitive, welcoming methodology, with certification in stages, and which values the subject’s path based on a hybrid teaching with welcoming. The term OFÉ, chosen to name the Institute, a word in Yorubá to designate a form of magic that makes a person light, to the point of floating in the wind and jumping very high, is a way of honoring our African ancestry and language and a way of representing all segments that did not have the same social and educational opportunities in the development of Brazilian society, with a commitment to take university technological professional education, with quality, to less privileged segments of society, in order to contribute to the reduction of educational and social dissymmetry. The word OPÔ, chosen to name the methodology, is a term in Yorubá, which designates fullness, plurality for all, a way of highlighting the possibility of offering university technological education for all. As a proposal to combat inequalities, due to the lack of opportunities, it will also be worked in the perspective of family welcoming, providing the dependents of students with the possibility of entering professional courses, associated with craftsmanship and gastronomy practices, available through the ÒNÀ core, which in Yorubá means path, road, access. Linked to OFÉ Institute, this center aims to develop competencies and skills to provide future generation of income and employability to the family nucleus, with a proposal to always act collectively and in solidarity.